Answer:
The equation of the tangent line passing through the point (-2,3) is
4 x + y +5 =0
Explanation:
Step(i):-
Given that the slope of the tangent
![m = (dy)/(dx) = x(y-1)](https://img.qammunity.org/2022/formulas/mathematics/high-school/36a83te4uzjyr8fpq7be4z7hl5rr00gwr5.png)
m = -2( 3-1) = -4
Given point x = -2
y = f(-2) =3
∴The given point ( x₁ , y₁) = ( -2 ,3)
Step(ii):-
The equation of the tangent line passing through the point (-2,3)
![y - y_(1) = m(x-x_(1) )](https://img.qammunity.org/2022/formulas/mathematics/high-school/f32rytp32voi5xcewxjxy01xhxoghodxac.png)
![y -3 = -4(x-(-2))](https://img.qammunity.org/2022/formulas/mathematics/high-school/xxzfb157ge9v7gn44ff8a740k5v526pgtl.png)
y -3 = -4( x+2)
y-3 = -4x -8
4x + y -3+8=0
4x +y +5=0
Step(iii):-
The equation of the tangent line passing through the point (-2,3) is
4 x + y +5 =0